PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN ZAMA HOMEWEAR DI MALANG - PUTRIA DEWI MASRUROH; YUNUS HANDOKO; IKE KUSDYAH RACHMAWAT (AKADEMIKA, 2022)
The purpose of this research is to find out and analyze; 1) The influence of brand image on purchasing decisions of Zama Homewear Malang. 2) the influence of brand trust on purchasing decisions for Zama Homewear Malang products, and 3) the influence of brand image and brand trust on purchasing decisions for Zama Homewear Malang products. The population in this study is Zama Homewear customers who shopped at least once and made transactions during November to January 2022, as many as 409 buyers. The sample size was taken as many as 80 respondents, with the sampling technique using the Slovin formula with proportional random sampling method. Data collection was carried out through the distribution of online questionnaires in the form of a google form with the distribution link being shared through the customer's whatsapp number. The analysis technique used is the multiple linear regression analysis method through SPSS 26. The results show that brand image and brand trust partially or simultaneously have a significant effect on purchasing decisions for Zama Homewear Malang products. Brand trust has a more dominant influence than brand image.